Synchronicity in Non-smooth Competitive Networks with Threshold Nonlinearities - Chialva, Ulises; Reartes, Walter (Journal of Applied Nonlinear Dynamics, 2026)
The synchronization of nodes is a widely reported phenomenon in a large variety of networks. However, the mechanisms that produce such behavior can not always be studied analytically. In this paper, certain non-smooth competitive networks with linear thresholds are studied with formal and numerical tools. We show that the symmetries of the network architecture allow to display and explain the synchronicity between the nodes. Finally it is demonstrated that in this type of non-smooth networks the synchronicity constitutes a bifurcation phenomenon related to the stability of limit cycles.